2020
DOI: 10.3389/fped.2019.00567
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of Fetal Models of Congenital Heart Disease Derived From Microfocus Computed Tomography: A Case Series

Abstract: This article presents a case series of n = 21 models of fetal cardiovascular anatomies obtained from post mortem microfocus computed tomography (micro-CT) data. The case series includes a broad range of diagnoses (e.g., tetralogy of Fallot, hypoplastic left heart syndrome, dextrocardia, double outlet right ventricle, atrio-ventricular septal defect) and cases also had a range of associated extra-cardiac malformations (e.g., VACTERL syndrome, central nervous system anomalies, renal anomalies). All cases were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…They underlined that the segmentation and printing processes are the same for normal and pathologic specimens, but reconstruction of complex anatomy may require expert guidance. Even if educational research and clinical implications were out of the aim of the study, the authors suggested that the 3D printing of fetal heart models could have a role in these scenarios [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They underlined that the segmentation and printing processes are the same for normal and pathologic specimens, but reconstruction of complex anatomy may require expert guidance. Even if educational research and clinical implications were out of the aim of the study, the authors suggested that the 3D printing of fetal heart models could have a role in these scenarios [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Contrast-enhanced micro-computed tomography (micro-CT) is one of the alternative methods that has proven to be feasible in the postmortem evaluation of the human fetal heart since the 8° WG, reaching adequate detection rate compared to the gold standard technique [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Besides the clinical domain, it can be used for educational and teaching purposes, having the potential to generate overriding medical and non-medical areas for future scientific and engineering advancements in the field of pediatric cardiology [ 35 , 36 , 37 , 38 , 39 , 40 ]. When compared to other non-invasive postmortem techniques, micro-CT seems to have a better balance between advantages and limitations for studying isolated fetal hearts [ 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] At present, applications of 3D printing in fetal cardiology are limited, yet the technique is appealing, as precise visualization of small structures is essential to achieve a correct diagnosis. 13 Some centers have adopted the technology and have published case reports to share their experiences with heart models. [6][7][8][9] Our study complements information on the feasibility of 3D printed fetal hearts and presents a series of complex cases of CHD, including conotruncal malformations and vascular ring abnormalities, among others.…”
Section: Discussionmentioning
confidence: 99%
“…These include medical education, surgical, and catheter‐based individualized procedural planning and manufacturing research for device innovation 8,10–12 . At present, applications of 3D printing in fetal cardiology are limited, yet the technique is appealing, as precise visualization of small structures is essential to achieve a correct diagnosis 13 . Some centers have adopted the technology and have published case reports to share their experiences with heart models 6–9 .…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, in the light of growing interest in 3D printing technology, particularly in the cardiovascular community, its use in obstetrics essentially increased over the last few years [ 112 ]. Due to the anatomical variability, the complexity of interventional/surgical repair is very high; thus, the modeling in the treatment strategy, particularly in congenital heart disease (CHD), warrants an individual approach in preoperative planning [ 112 ].…”
Section: Discipline Specific Applicationsmentioning
confidence: 99%